2007
DOI: 10.1111/j.1600-0536.2007.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

The local lymph node assay and the assessment of relative potency: status of validation

Abstract: For the prediction of skin sensitization potential, the local lymph node assay (LLNA) is a fully validated alternative to guinea-pig tests. More recently, information from LLNA dose-response analyses has been used to assess the relative potency of skin sensitizing chemicals. These data are then deployed for risk assessment and risk management. In this commentary, the utility and validity of these relative potency measurements are reviewed. It is concluded that the LLNA does provide a valuable assessment of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 49 publications
5
50
1
Order By: Relevance
“…According to our EC 3 results, formaldehyde and PPD can be classified as strong allergens, cinnamal a moderate sensitizer, and eugenol a weak sensitizer. Such results were in good agreement with previous classifications obtained by Kimber et al (2003) and Basketter et al (2007) using the standard radioactive LLNA.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…According to our EC 3 results, formaldehyde and PPD can be classified as strong allergens, cinnamal a moderate sensitizer, and eugenol a weak sensitizer. Such results were in good agreement with previous classifications obtained by Kimber et al (2003) and Basketter et al (2007) using the standard radioactive LLNA.…”
Section: Discussionsupporting
confidence: 82%
“…The data for all OD 450, SI, and EC 3 values from the current ex vivo BrdU labeling studies are presented in Table 2. EC 3 values for these four agents when using a standard LLNA method Basketter et al, 2007) and the ex-vivo LLNA-BrdU method are shown in Table 3.…”
Section: Lymph Node-related Parameters Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…an SI of 3. If the datapoints lying immediately above and below the SI value of 3 have the coordinates (a, b) and (c, d), respectively, then the EC 3 value may be calculated using the following equation (Basketter et al, 1999b(Basketter et al, , 2007:…”
Section: Calculation Of Ec 3 Valuementioning
confidence: 99%